Pengaruh Profitabilitas, Investasi Aktiva Lancar, Perputaran Persediaan, dan Perputaran Piutang terhadap Tingkat Pendanaan Jangka Pendek Perusahaan Retail yang Listing di BEI Periode 2004-2008 - Suciani, Suciani (BISMA (Bisnis dan Manajemen), 2018)
To overcome the complexity of competition in the market of retail industry, retail company should make an optimal financing decision. This research focus on short term debt financing of Retail company which is listing in Indonesia Stock Exchange during period (of time) 2004-2008. At that moment, the SBI rates showed progressively trend and degradation of customer purchasing power because of increasing price of goods and competitor of other retail company. Based on the empirical fact, this research aims to examine the influences of profitability, current asset investment, inventory turnover, and receivable turnover to Short Term Debt Financing of retail companies. The technique analyze used multiple linear regression. The result of regression test concluded that simultaneously profitability, current asset investment, inventory turnover, and receivable turnover had significantly influences for short-term debt financing. Also in partially test, profitability, current asset investment, inventory turnover, and receivable turnover also had significantly influences for short-term debt financing